Agri-Environmental Issues in the National Sustainable Development Strategy of the Member States of the Enlarged EU - Gáthy, Andrea (Acta Agraria Debreceniensis, 2005)
In preparation for the World Summit on Sustainable Development (Johannesburg), almost all EU member-states and some accession countries presented their national strategies for sustainable development (NSSD) during the summer of 2002. Along with other countries, Hungary is only now setting up this important document. Everywhere during the last decade, as in the EU countries, the intention was to involve the environmental problems into other political questions (agricultural, energy and transport policy, etc.). Today the strategy-builders have given up the sectoral view because of difficulties and setbacks, and use a view aiming the problem. Agri-environmental issues appear as the elements of sustainability in the national strategies. For example, in accordance with the danger of global warming, the emission of green-house gasses of agriculture; in line with eco-efficiency, the production of renewable raw materials and energy sources originating from agriculture, and, in relation to changing lifestyle, food-safety and the future of biological agriculture will be disputed. With this study, I investigate the main characteristics of sustainable development strategies at both the EU level and at the level of the different member states from an agri-environmental point of view.